LABORATORY MANAGEMENT FROM THE PERSPECTIVE OF PRINCIPALS, SCIENCE TEACHERS AND LEARNERS AT UPT SPF SMP NEGERI 24 MAKASSAR - Samputri, Salma; Arif, Rifda Nur Hikmahwati; Amir, Muh. Idham; Ramadhani, Reski (MO.RI Publishing, 2024)
This study aims to describe: 1) laboratory management from the perspective of school principals 2) laboratory management from the perspective of science teachers 3) laboratory management from the perspective of students. The research method of research used is the survey method. The study population was all people in UPT SPF SMPN 24 Makassar. The sampling technique used was random sampling, using the slovin formula with a sample of 120 students, sampling teachers and principals using saturated sampling techniques. Data collection techniques using questionnaires. Data analysis techniques using descriptive statistics. The results showed that: 1) laboratory management in terms of the principal's perspective on the evaluation aspect, the majority chose the answer “Always” as much as 66.7%, 2) laboratory management in terms of the perspective of science teachers in the planning aspect, the majority chose the answer “Always” as much as 51.5%, the implementation aspect, the majority chose the answer “Often” as much as 35.29%, and the evaluation aspect, the majority chose the answer “Rarely” as much as 40.74%, 3) laboratory management in terms of the perspective of students in the implementation aspect, the majority chose the answer “Always” as much as 27.06% in UPT SPF SMPN 24 Makassar.